2007
DOI: 10.1111/j.1349-7006.2007.00626.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of early preneoplastic events in the rat liver by the somatostatin analog lanreotide

Abstract: Hepatocellular carcinoma (HCC) is the third most common cause of cancer-related death, and its incidence is increasing worldwide. Due to the known risk factors (mainly hepatitis B and C viruses), we believe there is a rationale for a chemopreventive approach to treat HCC. Here, based on described in vitro data, we evaluated the preventive effects of lanreotide, a somatostatin analog, on the induction of early carcinogenic events. We monitored preneoplastic foci induced by a two-stage initiation/promotion model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
0
9
1
Order By: Relevance
“…In the two-stage hepatocarcinogenesis model, tumor promotion treatment reduces apoptosis within preneoplastic GST-P + liver cell foci (Borbath et al, 2007). However, in the present study we found that both PBO and MP-promoted livers increased both proliferation and apoptosis within GST-P + liver cell foci.…”
Section: Discussioncontrasting
confidence: 86%
“…In the two-stage hepatocarcinogenesis model, tumor promotion treatment reduces apoptosis within preneoplastic GST-P + liver cell foci (Borbath et al, 2007). However, in the present study we found that both PBO and MP-promoted livers increased both proliferation and apoptosis within GST-P + liver cell foci.…”
Section: Discussioncontrasting
confidence: 86%
“…For example, substance P promotes tumor cell proliferation and angiogenesis . Alternatively, somatostatin inhibits the tumor growth, and, thus, somatostatin analogue is used effectively for treatment of liver or pancreatic cancer . Overexpression of VIP receptors VPAC1 and VPAC2 is seen in many human cancers .…”
Section: Discussionmentioning
confidence: 99%
“…20 Alternatively, somatostatin inhibits the tumor growth, and, thus, somatostatin analogue is used effectively for treatment of liver or pancreatic cancer. 21,22 Overexpression of VIP receptors VPAC1…”
Section: Discussionmentioning
confidence: 99%
“…1 Therefore, chemoprevention could play a role in the therapy of HCC. 2 Histone deacetylase inhibitors (HDACi) have emerged as potential anticancer agents. Recent interest in HDACi has expanded into the realm of cancer chemoprevention, with evidence that dietary compounds act as weak ligands for HDAC and exhibit HDAC inhibitory activity.…”
mentioning
confidence: 99%